TRENDS IN THE DEVELOPMENT OF ECOTOURISM IN LATVIA - LEITIS, Eriks (Journal of Environmental Management and Tourism; Vol 2 No 2 (2011): JEMT Volume II Issue 2(4) Winter 2011, 2011)
Public understanding of ecotourism is reported to vary widely in Latvia. Today, ecotourism is becoming more and more popular in Latvia and is seen as an important part of the process of tourism development and is also included in the documents related to the tourism policy. Ecotourism in Latvia is still a novelty, thus making it a necessity to recognize it’s trends and to develop an effective ecotourism model, which will then serve as an important tool for protecting the environment and to promote the welfare of local residents. It will also serve to build awareness of ecotourism through further discourse. This study which serves as the basis for the creation of the ecotourism model covers the Natura 2000 territories in Latvia in the context of the appropriate national legal acts and strategies, the development of the definition of ecotourism and with the co-operation of the parties involved. Ecotourism is able to contribute to biodiversity, local welfare and to ensure ecosystem function in Latvia through the complicated process of fulfilment of the established criteria for a valid ecotourism.